"Crevasse" Lesions: A Unique Pattern of Femoral Head Chondral Damage. (January 2014) - Philippon, Marc J.; Goljan, Peter; Devitt, Brian M.; Peixoto, Lourenço P.
Objective: The purpose of this article is to report on a distinctive pattern of linear femoral head chondral lesions that were observed in 7 patients who underwent hip arthroscopy for the treatment of mixed-type femoroacetabular impingement (FAI). Design : Between 2010 and 2012, 702 patients were treated with hip arthroscopy at our institution for symptomatic FAI. Among those patients, 7 were found to have a unique vertical chondral fissure located on the posterior femoral head. A retrospective review of the preoperative history, physical examination, and radiographic findings in addition to the intraoperative findings and surgical procedures performed was carried out for each patient. Results : All patients were diagnosed with mixed-type FAI by dynamic examination intraoperatively. The femoral head cartilage lesions were noted to be both linear and deep and resembled the appearance of a crevasse. Three of the 7 patients in whom these lesions were identified reported an acute event preceding their pain. Of the other 4 patients, 3 were involved in sports that involved vigorous rotational hip movements: golf, tennis, and wrestling. Notably, none of these lesions were identifiable on preoperative 3-T MRI scans. Conclusions : This series reports on a previously undefined femoral head cartilage lesion. It is hypothesized that increased pathologic translational movements and perching of the femoral head on the posterior rim of the acetabulum create this pattern of chondral damage. Recognition of this pattern of damage on the femoral head is important in the setting of mixed-type FAI.